1990
DOI: 10.1007/bf01186818
|View full text |Cite
|
Sign up to set email alerts
|

Retention of J1/tenascin and the polysialylated form of the neural cell adhesion molecule (N-CAM) in the adult olfactory bulb

Abstract: To gain insight into the cellular and molecular mechanisms underlying neurogenesis in adult mouse olfactory bulb, several adhesion molecules expressed by glial cells and neurons were investigated. In the germinal zone of the olfactory bulb, the subependymal layer of the rostral region of the lateral ventricles, two adhesion molecules are detectable that are characteristic of early morphogenetic events: J1/tenascin and the polysialylated form, the so-called embryonic form, of N-CAM. The polysialylated form of N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
57
0

Year Published

1994
1994
2004
2004

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(62 citation statements)
references
References 65 publications
5
57
0
Order By: Relevance
“…More likely, the results indicate that those synapses expressing PSA-NCAM were preferentially affected by the NMDA antagonist. This hypothesis is supported by evidence that PSA-NCAM expression is typically associated with synapses which are less mature and retain a higher level of plasticity [Bonfanti et al, 1992;Miragall et al, 1990;Muller et al, 1996;Rousselot and Nottebohm, 1995;Seki and Arai, 1993;Tang and Landmesser, 1993;Williams et al, 1996;Rutishauser and Landmesser, 1996]. Evidence suggests that PSA-NCAM is critical for LTP and that LTP plays a role in synaptic stabilization [Bailey et al, 1992;Edwards, 1995;Buchs and Muller, 1996;Geinisman et al, 1996].…”
Section: Polysialylated Form Of the Neural Cell Adhesion Molecule Andsupporting
confidence: 60%
See 1 more Smart Citation
“…More likely, the results indicate that those synapses expressing PSA-NCAM were preferentially affected by the NMDA antagonist. This hypothesis is supported by evidence that PSA-NCAM expression is typically associated with synapses which are less mature and retain a higher level of plasticity [Bonfanti et al, 1992;Miragall et al, 1990;Muller et al, 1996;Rousselot and Nottebohm, 1995;Seki and Arai, 1993;Tang and Landmesser, 1993;Williams et al, 1996;Rutishauser and Landmesser, 1996]. Evidence suggests that PSA-NCAM is critical for LTP and that LTP plays a role in synaptic stabilization [Bailey et al, 1992;Edwards, 1995;Buchs and Muller, 1996;Geinisman et al, 1996].…”
Section: Polysialylated Form Of the Neural Cell Adhesion Molecule Andsupporting
confidence: 60%
“…Indeed, the removal of PSA from NCAM interferes with the induction of LTP and long-term depression (LTD) in the hippocampus and results in a decrease in synapses in developing chick muscle [Tang and Landmesser, 1993]. Accordingly, expression of PSA-NCAM is correlated with a high level of both axonal and synaptic plasticity [Aaron and Chesselet, 1989;Bonfanti et al, 1992;Miragall et al, 1990;Muller et al, 1996;Rousselot and Nottebohm, 1995;Seki and Arai, 1993;Williams et al, 1996; review by Rutishauser and Landmesser, 1996].…”
Section: Polysialylated Form Of the Neural Cell Adhesion Molecule Andmentioning
confidence: 99%
“…As has been shown by Western blot analysis, during early embryogenesis of chicken and frag N-CAM is expressed in its lightly sialylated forms (L-N-CAM), during late embryonie development predominantly in its heavily sialylated forms (H-N-CAM), while during early postnatal development H~N-CAM is again converted to L-N-CAM (Levi et al, 1987;. The scheme foragenerat conversion ofH-to L-N-CAM, at least during postnatal development, is clearly too simplistic as it has been shown that H-N-CAM is also expressed in particular parts of the body during adulthood, for ~xample in the hypothalamo-neurohypophysal system (Theodosis et al, 1991), optie nerve, retina (Bartsch et al, 1990), and the olfactory bulb (Miragall et al , 1988(Miragall et al , , 1990.…”
Section: Introductionmentioning
confidence: 99%
“…Besides symmetric divisions, B-cells generate a transit amplifying population of cells (C-cells) that expresses Nestin, Dlx2, and Dlx1 (Doetsch et al, 1999;Saino-Saito et al, 2003). C-cells give rise to a third type of precursor, the migrating neuroblasts (A-cells), which express TUJ1, DLX2, DLX1, and polysialylated-neural cell adhesion molecule (Miragall et al, 1990;Bonfanti and Theodosis, 1994;Ben-Hur et al, 1998;Saino-Saito et al, 2003). These cells delaminate in the anterior SVZ (SVZa) and migrate toward the OB at ϳ30 m/hr, through chain migration (Lois et al, 1996;GarciaVerdugo et al, 1998).…”
Section: Introductionmentioning
confidence: 99%